Volumetric Interpretation of Protein Adsorption: Interfacial Packing of Protein Adsorbed to Hydrophobic Surfaces from Surface-Saturating Solution Concentrations - Kao, Ping (2010)
The maximum capacity of a hydrophobic adsorbent is interpreted in terms of square or hexagonal (cubic and face-centered-cubic, FCC) interfacial packing models of adsorbed blood proteins in a way that accommodates experimental measurements by the solution-depletion method and quartz-crystal-microbalance (QCM) for the human proteins serum albumin (HSA, 66 kDa), immunoglobulin G (IgG, 160 kDa), fibrinogen (Fib, 341 kDa), and immunoglobulin M (IgM, 1000 kDa). A simple analysis shows that adsorbent capacity is capped by a fixed mass/volume (e.g. mg/mL) surface-region (interphase) concentration and not molar concentration. Nearly analytical agreement between the packing models and experiment suggests that, at surface saturation, above-mentioned proteins assemble within the interphase in a manner that approximates a well-ordered array. HSA saturates a hydrophobic adsorbent with the equivalent of a single square-or-hexagonally-packed layer of hydrated molecules whereas the larger proteins occupy two-or-more layers, depending on the specific protein under consideration and analytical method used to measure adsorbate mass (solution depletion or QCM). Square-or-hexagonal (cubic and FCC) packing models cannot be clearly distinguished by comparison to experimental data. QCM measurement of adsorbent capacity is shown to be significantly different than that measured by solution depletion for similar hydrophobic adsorbents. The underlying reason is traced to the fact that QCM measures contribution of both core protein, water of hydration, and interphase water whereas solution depletion measures only the contribution of core protein. It is further shown that thickness of the interphase directly measured by QCM systematically exceeds that inferred from solution-depletion measurements, presumably because the static model used to interpret solution depletion does not accurately capture the complexities of the viscoelastic interfacial environment probed by QCM.